Muskuloskeletal disorders in upper limbs in dental students: exposure level to risk factors - Garcia, Patrícia Petromilli Nordi Sasso; Pinelli, Camila; Derceli, Juliana dos Reis; Campos, Juliana Alvares Duarte Bonini [UNESP] (My University, 2012)
Aim: This study assessed the risk factors of undergraduate students to develop musculoskeletaldisorders (MSD) in the upper limbs, regarding gender, type of dental clinical procedure, mouthregion treated, and the four-handed dentistry practice. Methods: Dental students enrolled in the8th semester in the Araraquara School of Dentistry, UNESP, Brazil, were photographed whilepracticing 283 dental procedures. The Rapid Upper Limb Assessment (RULA) method was usedto evaluate the working postures of each student. The photographs were evaluated and a finalrisk score was attributed to each analyzed procedure. The prevalence of risk factors of developingMSD was estimated by point and by 95% confidence interval. The association between the riskfactor of developing disorders and variables of interest were assessed by the chi-square test witha significance level of 5%. Results: The risk factors of developing MSD were high, regardingmost dental procedures performed by the undergraduate students (score 5: 7.07%, CI95%: 4.08-10.06%; score 6: 62.54%, CI95%: 56.90-68.18%). There was no significant association betweenthe RULA final score and gender (p=0.559), and type of dental procedure (p=0.205), and mouthregions by arch (p=0.110) or hemi-arch (p=0.560), and the use of four-handed dentistry (p=0.366).Conclusions: It can be concluded that gender, type of dental clinical procedure, mouth regiontreated, and practice of four-handed dentistry did not influence the risk of developing MSD in theupper limbs among the dental students evaluated; however, they are at a high risk of developingsuch disorders.(AU).
Keywords: Dentistry; Occupational Health; Students, Dental; Human Engineering